CONTRIBUIÇÕES DA TEORIA DA APRENDIZAGEM SIGNIFICATIVA E DA MODELAGEM MATEMÁTICA PARA O ESTUDO DE FUNÇÕES - Iaronka, Clessi Fátima (2008)
This essay presents the results of a survey which had been taken with the students of the first stage of the Technological College, the area of Gerencia de Obras from Universidade Tecnológica do Paraná- UTFPR - Campus Pato Branco PR. The main goal of the present investigation was to analyze the possibilities on acquisition of basic concepts over Function, using the mathematical mould, under the view of Ausubel s theory for meaningful learning. The utilized methodology of the research, associated to the pedagogical procedures of the mathematics mould, made possible to that the students who were involved in the present study, a meaningful built and assimilation of basic concepts over functions. The results of the investigation showed that the integration of specific mathematical activities with the students reality can really contribute to a meaningful learning of the basic concepts of functions, due to the methodological process used to offer the students the opportunities to deal with real situations and situations which are interesting to them.